2018
DOI: 10.1101/333849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep feature selection for Identification of Essential Proteins of Learning and Memory in Mouse Model of Down Syndrome

Abstract: Down syndrome is a chromosomal abnormality related to intellectual disabilities that affects 0.1% of live births worldwide. It occurs when an individual has a full or partial extra copy of chromosome 21. This chromosome trisomy results in the overexpression of genes that is believed to be sufficient to interfere normal pathways and normal responses to stimulation, causing learning and memory deficiency. Therefore, by studying these proteins and the disturbance in pathways that are involved in learning and memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…These data will allow for the early diagnosis of DS. Absolutely, there are many popular molecular techniques that can be used to detect prenatal diagnostic markers such as Fisher score, Chi score, and correlation-based subset [12]. We will consider using these molecular techniques for further research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data will allow for the early diagnosis of DS. Absolutely, there are many popular molecular techniques that can be used to detect prenatal diagnostic markers such as Fisher score, Chi score, and correlation-based subset [12]. We will consider using these molecular techniques for further research.…”
Section: Resultsmentioning
confidence: 99%
“…At present, many studies have studied the relationship between proteome and DS by various molecular techniques. Abdeldayem et al [12]. used Fisher score, Chi score, and correlation-based subset to select the most important proteins related to learning and memory from mouse model of DS.…”
Section: Discussionmentioning
confidence: 99%
“…Sara et al 27 proposed a quantitative approach to investigate protein expression in order to identify important differences in protein levels in mice exposed to CFC by using machine learning feature selection algorithms. Four different selection models are used such as Fisher score, Chi score, correlation-based approach and Deep feature selection (D-DFS) proposed by Yifeng et al 28 .…”
Section: Related Workmentioning
confidence: 99%
“…An increment of accuracy with their reduced protein subset (98% by applying Random Forest) was shown compared to the previous models built from the original protein data-sets.On the other hand, Kulan et al 24 argues that Naïve Bayes feature selection method could provide a better protein subset rather than AdaBoost used by B.Feng et al Same as the previous work, they reduced the dataset from 77 proteins to 30 and applied Random Forest, Deep Neural Network, and SVM for classification. They compared their results with B. Feng et al, and showed that their method gives a higher accuracy, by reaching 99% accuracy using DNN.Sara et al 27 proposed a quantitative approach to investigate protein expression in order to identify important differences in protein levels in mice exposed to CFC by using machine learning feature selection algorithms. Four different selection models are used such as Fisher score, Chi score, correlation-based approach and Deep feature selection (D-DFS) proposed by Yifeng et al 28 .…”
mentioning
confidence: 99%